Metabolic interactions in asthma
Metabolomics can be used to explore altered metabolic pathways in asthma, giving insights into its pathophysiology. We aimed to review how metabolomics has been used to understand asthma by describing metabolic pathways under research and discussing clinical implications. The search was performed in PubMed, and studies published since 2000 using a metabolomics approach, were included. A total of 32 studies were analysed. Pathways related with cellular energy homeostasis, lipid metabolism and oxidative stress, immune and inflammatory processes and others were altered. Initial studies focused on biomarker discovery. But, metabolomics can be used to evaluate drug effects on specific pathways, to highlight pathways that can further develop in new targeted treatments and to identify differences according to asthma severity and phenotypes.